A novel experimental design approach to generating orbital angular momentum waves using wearable textile antenna for sub-6 GHz 5G - Shehab Khan Noor; Arif Mawardi Ismail; Nassrin I. M. Elamin; Mohd Najib Mohd Yasin; Mohamed Nasrun Osman; Ping Jack Soh; Nurulazlina Ramli; Ali H. Rambe; Adel Y. I. Ashyap (PLoS ONE, 2025)
This paper presents a novel wearable textile array antenna designed to generate Orbital Angular Momentum (OAM) waves with mode + 1 at 3.5 GHz (3.4 to 3.6 GHz) of the sub-6 GHz 5G New Radio (NR) band. The proposed antenna is based on a uniform circular array (UCA) of four microstrip patch antennas on a felt textile substrate. Compared to previous works involving the use of hard substrates for OAM waves generation, this work explored the use of flexible textile substrates to generate OAM waves for the first time to the best of our knowledge. The overall dimension of the array antenna is 170 ×  156 mm2 while the dimension of each element is 35 ×  35.7 mm2. In order to control the phase and generate OAM waves, the proposed antenna was designed using a felt textile substrate and meandering lines of various lengths connecting the radiating patches. 1.48λ was the separation between radiating patches in order to prevent mutual coupling between them. The antenna was fabricated and measured prior to comparison to simulations to validate this feature. It achieved a measured gain of 3.18 dBi with a bandwidth of 430 MHz (3.24 to 3.67 GHz). Additionally, mode purity analysis was carried out to verify the generation of OAM mode + 1, and the purity obtained was 52.12%. This paper also covered the effect of bending on OAM waves characteristics and the use of airgap technique to enhance the antenna gain. The antenna gain increased from 3.762 dBi to 5.327 dBi by using 1 mm airgap without affecting the mode purity. Furthermore, as per the Specific Absorption Rate (SAR) obtained, it is found that the proposed antenna is safe for on-body use. The novel approach in generating OAM using patch array antenna with flexible substrate by replacing conventional hard substrate has opened up new scope of research in wearable textile antenna domain. The proposed antenna has simple structure, easy to design, fabricate and deploy on human body and has important significance in scaling up this design to generate multiple OAM modes for carrying multiple signals simultaneously.